Enhancing Potency and Selectivity of a DC‐SIGN Glycomimetic Ligand by Fragment‐Based Design: Structural Basis. Issue 64 (18th October 2019) - Medve, Laura; Achilli, Silvia; Guzman‐Caldentey, Joan; Thépaut, Michel; Senaldi, Luca; Le Roy, Aline; Sattin, Sara; Ebel, Christine; Vivès, Corinne; Martin‐Santamaria, Sonsoles; Bernardi, Anna; Fieschi, Franck
Abstract: Chemical modification of pseudo‐dimannoside ligands guided by fragment‐based design allowed for the exploitation of an ammonium‐binding region in the vicinity of the mannose‐binding site of DC‐SIGN, leading to the synthesis of a glycomimetic antagonist (compound 16 ) of unprecedented affinity and selectivity against the related lectin langerin. Here, the computational design of pseudo‐dimannoside derivatives as DC‐SIGN ligands, their synthesis, their evaluation as DC‐SIGN selective antagonists, the biophysical characterization of the DC‐SIGN/16 complex, and the structural basis for the ligand activity are presented. On the way to the characterization of this ligand, an unusual bridging interaction within the crystals shed light on the plasticity and potential secondary binding sites within the DC‐SIGN carbohydrate recognition domain. Abstract : Fragment‐based design : A high affinity monovalent DC‐SIGN ligand was obtained by targeting an ammonium‐binding pocket identified by virtual screening. The structural basis of its activity was elucidated by X‐ray crystallography, also unveiling an unusual bridging interaction within the crystals.